Green Innovation, Managerial Concern and Firm Performance: An Empirical Study. (30th October 2017) - Tang, Mingfeng; Walsh, Grace; Lerner, Daniel; Fitza, Markus A.; Li, Qiaohua
Abstract: Extant literature, while often suggesting a positive link between green innovation and firm performance, is inconclusive. Moreover, the possibly moderating role of management has not been sufficiently considered. Using a unique dataset sampling 188 manufacturing firms in China, we examine how managerial concern (for green issues) moderates the relationship between green innovation and firm performance. We find that green process innovation and green product innovation both significantly (positively) predict firm performance, when not considering managerial concern for the environment. Once managerial concern is included, we observe that it compounds the positive effect of green process innovation on firm performance – but not product innovation, which no longer explains significant unique variance in firm performance. The findings hold various implications for future research and business policy. Copyright © 2017 John Wiley & Sons, Ltd and ERP Environment